CIVIL SOCIETY DAN KERUKUNAN UMAT BERAGAMA: TAWARAN PENDEKATAN - W A H I D K H O Z I N (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Conflicts among religion adherents have been never really overcome until now. Otherwise, the escalation of conflicts highly increased. To solve the problem, some approaches applied. More than ever today, the approach to the formulation of religious harmony has come from The Ministry of Religious Affairs to the elite of religious leaders. In the fact, the top-down approach has not really met to the grass root (common people). In line with the advance of civil society awareness such as mutual tolerance, respect, peace building, and egalitarian values at the level of community organization, it is worthy to apply a new approach of community-based religious harmony. This article proposes civil society as alternative approach to manage community-based religious harmony.